Resource book to improve vocabulary skill in students of eighth grade at escuela de educación básica Trece de Abril La Libertad, province of Santa Elena 201 -2016. - Urrunaga León, Gloria Geomar (2016)
This project was created to encourage participation of young students in the process of learning the English language. This is a way of contributing to their integral development, using strategies, didactic activities and motivational techniques to facilitate language learning. The main problem observed in English teaching is the deficiency and inadequate application of teaching techniques and methodologies in the classroom. To give solution to this problematic, the teacher needs to use tools and strategies to help increase vocabulary skills the students. This study was supported by the classroom observation, the techniques and methodological strategies utilized by the English teacher allowed the development of a didactic tool such as a resource book to enhance vocabulary skills in learners, which will facilitate the improvement of the teaching-learning process. This research is focused on the importance of vocabulary skills and based on four fundamental axes: motivation, constructive method, didactic activities and teaching vocabulary. Several aspects of each methodology were taken into consideration to design and to develop this Resource Book. This research involved the eighth grade students at escuela de educación básica Trece de Abril as the main actors of this investigation and the school principal. The author had a period of three months to frame this project, the initial data was gathered through a preoral and written test, interviews and a questionnaire.